Educación Superior y desarrollo económico y social en Cuba: a propósito de la "Tercera Misión - Isarelis Pérez Ones; Jorge Núñez Jover (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2009)
En este documento se muestra mediante un estudio de caso cómo la universidad cubana se involucra de modo directo con el desarrollo económico y social del país. Esta exposición se relaciona con el debate internacional sobre la "Tercera Misión" de la universidad, a partir de la peculiar experiencia cubana. This paper presents case studies on how Cuban universities have increasingly become directly involved with the economic and social development of the country. The paper shows how Cuban universities, from the late 1980s and early 1990s, started reorientation and organization of their scientific research, becoming more directly and intensely involved in the economic and social development of the country. In this connection, special reference is made to the case of a research group at the University of Havana: the Laboratory of Synthetic Antigens. This group developed the first synthetic vaccine for human use approved in the world. In the article, public policies involved in this success as well as different obstacles are discussed. These obstacles demonstrate the difficulties and challenges that universities face when carrying out research and innovation activities related to economic and social development.